Hubungan Hiperemesis terhadap Stress Ibu Hamil Trimester I Di Wilayah Kerja Puskesmas Parigi Kecamatan Takkalalla Kabupaten Wajo - Rosmiati Rosmiati (Lembaga Layanan Pendidikan Tinggi (LL-DIKTI) Wilayah IX Sulawesi, 2020)
Hyperemesis is a very frequent nausea and vomiting during the first half of pregnancy. Usually nausea and vomiting begins between the late first and second periods and continues for about 14 weeks. Nausea and vomiting are usually more severe in the morning, but may continue throughout the day. This study aims to determine the relationship between hyperemesis and the occurrence of stress in pregnant women in the first trimester in the work area of ​​the parigi health center, Takkalalla sub-district, Wajo district. This study used a quantitative study using the Accidental Sampling research method, the population in this study was 101 pregnant women. The sampling technique used was accidental sampling. Data collection was obtained using a questionnaire. Analysis of the relationship using the chi square test. The results of this study indicate that there were 7 respondents (46.7%) who had experienced hyperemesis, while 6 respondents (40.0%) had experienced stress. The results of statistical tests showed that hyperemesis (p = 0.001) so it was concluded that there was a relationship between hyperemesis and stress in pregnant women in the first trimester in the work area of ​​the Parigi Public Health Center, Takkallalla District, Wajo District. Thus pregnant women who experience hyperemesis and stress during pregnancy are expected to continue to control their health .